Comparison of IL-10 and MCP-1-7ND gene transfer with AAV9 vectors for protection from murine autoimmune myocarditis - Kaya, Ziya; Leib, Christoph; Werfel, Stanislas; Göser, Stefan; Öttl, Renate; Leuchs, Barbara; Pfitzer, Gabriele; Katus, Hugo; Müller, Oliver J. (Cardiovascular research, 2011)
Overexpression of therapeutic genes with potential disease-limiting effects, specifically at the site of inflammation, remains a major clinical challenge. In this study, we investigate the potential of adeno-associated virus (AAV)-9-mediated cardiac expression of the anti-inflammatory mediators interleukin (IL)-10 and a dominant-negative inhibitor of monocyte chemoattractant protein-1 (MCP1-7ND) on prevention of autoimmune myocarditis.Autoimmune myocarditis was induced by immunizing A/J mice with subcutaneous injection of 120 µg cardiac Troponin I (cTnI) on Days 0, 7, and 14. Two weeks prior to initial immunization, each mouse received a single systemic dose of 1012 AAV9 vectors carrying the coding sequence of IL-10 or MCP1-7ND transcriptionally targeted to the heart. Mice were sacrificed 28 days after initial immunization for further analysis. Only expression of IL-10 resulted in a highly significant decrease in myocardial inflammation and fibrosis, as well as an increased ejection fraction compared with controls. Further analyses of cytokine profiles of cTnI-stimulated splenocytes from IL-10 and MCP1-7ND-treated mice revealed significant alterations compared with controls. In addition, transcript levels of chemokine receptor CCR4 and T-cell activation gene were significantly reduced in hearts of IL-10-treated mice as determined by quantitative real-time PCR.Our study suggests that cardiac expression of IL-10 with AAV9 vectors is a promising therapeutic approach for autoimmune myocarditis.